High Temperature Induced Glume Closure Resulted in Lower Fertility in Hybrid Rice Seed Production - Yan, Haoliang; Zhang, Binglin; Zhang, Yunbo; Chen, Xinlan; Xiong, Hui; Matsui, Tsutomu; Tian, Xiaohai (Frontiers in Plant Science, 2017)
Predicted climate changes, in particular, the increased dimension and frequency of heat waves, are expected to affect crop growth in the future seriously. Hybrid rice relies on seed production from male sterile and restorer lines. Experiments were conducted over two consecutive years to compare the high temperature tolerance of parents of different hybrid rice combinations, in terms of fertility rate, flowering pattern, pollination and physiological parameters of the lodicule. Three male sterile lines and a broad compatibility restorer line (as pollen donor and conventional variety as well) were grown to heading stage and then treated with average daily temperatures of 26 °C (range 23-30 °C), 28 °C (25-32 °C) and 30°C (26-34 °C) respectively continued for 5-7 days each in a natural light phytotron which simulated the local typical high temperature weather in the field. The results indicated that male sterile lines were more sensitive to high temperature than the restorer line for fertility rate, and the sensitivity varied between varieties. The fertility rate of the restorer line was maintained at about 90% under the high temperature treatments, while it decreased in the male sterile lines by 23.3% and 48.1% at 28 °C and 30 °C, respectively. The fertility rate of the most sensitive line declined by 70%, and the tolerant line declined by 34% at 30 °C. Glume closure in the male sterile lines was a major reason for the reduced fertility rate under high temperature, which is closely correlated with carbohydrates content and the vascular bundle pattern in the lodicule. The present study identified a useful trait to select male sterile lines with high temperature tolerance for seed production.